Influence of Silver Nanoparticles on the Biological Indicators of Haplic Chernozem - Sergey Kolesnikov; Natalia Tsepina; Tatiana Minnikova; Kamil Kazeev; Saglara Mandzhieva; Svetlana Sushkova; Tatiana Minkina; Mahmoud Mazarji; Rupesh Kumar Singh; Vishnu D. Rajput (Plants, 2021)
In recent years, silver nanoparticles (AgNPs) are increasingly used in various industries due to their antibacterial properties, which lead to an increase in pollution of the environment and soil ecosystems. However, the ecological effects of soil pollution by AgNPs were poorly studied than that with AgNPs of other metal-based NPs. The aim of this study is to assess the influence of AgNPs on the biological properties of Haplic Chernozem. Silver was introduced into the soil in the form of AgNPs with a concentration of 0.5; 1; 5; 10; 50, and 100 mg/kg in laboratory conditions. The influence of AgNPs on the biological properties of Haplic Chernozem was assessed 30 days after contamination. The degree of reduction in biological properties depends on the AgNPs concentration in the soil. This study showed that the sensitivity to contamination by AgNPs in the total number of bacteria and enzymatic activity was more than that in the abundance of bacteria of the genus Azotobacter. The integrated index of biological state (IIBS) of Haplic Chernozem was decreased by contamination with AgNPs. Silver nanoparticles in the concentration of 10 mg/kg caused a decrease in the indicator by 13% relative to the control. It also decreased IIBS by doses of 50 and 100 mg/kg by 22 and 27% relative to the control. All used biological indicators could be used for biomonitoring, biodiagnosis, bioindication, and regulation of ecological condition of soil contamination by AgNPs.